Struktur Komunitas Hama Pemakan Daun Kubis dan Investigasi Musuh Alaminya - KETUT AYU YULIADHI; PUTU SUDIARTA (Fakultas Pertanian Universitas Udayana, 2012)
The data concerning the community of pests that eat and destroy cabbage leaves in Bali has notbeen available yet. However, it is required for the pest control purposes. The aim of the research wasto investigate the structure of pest community that eat and destroy cabbage leaves and to find out theirnatural enemies for controlling the pests. Samples of the pest were collected from the cabbage plantsthat were treated with insecticide and without insecticide (control). The results show that the phytophageinsects that found on both treatments of growing cabbages were Plutella xylostella, Crocidolomiapavonana, Spodoptera litura, Helicoverpa armigera, Chrysodiexis orichalcea, and Aphis brassicae.Natural enemies that found on that area were parasitoid larva Plutella Diadegma semiclausum andpredator Crocidolomia pavonana, Sycanus dichotomus pdf (secured).